SARS-CoV-2: impact on, risk assessment and countermeasures in German Eye Banks - Trigaux, Celine; Salla, Sabine; Schroeter, Jan; Tourtas, Theofilos; Thomasen, Henning; Maier, Philip; Hellwinkel, Olaf J. C.; Wittmershaus, Ilka; Merz, Patrick; Seitz, Berthold; Nölle, Bernhard; Schrage, Norbert; et al. (Current eye research, 2021)
Since the beginning of the COVID-19 pandemic there has been some debate regarding the risk of transmission through tissue transplantation and tissue banking processes.To analyze the changes that SARS-CoV-2 has caused regarding the harvesting of corneal donor tissue and eye bank activities in Germany.